2007
DOI: 10.1093/intimm/dxm091
|View full text |Cite
|
Sign up to set email alerts
|

Programmed death-1 blockade enhances expansion and functional capacity of human melanoma antigen-specific CTLs

Abstract: Negative co-stimulatory signaling mediated via cell surface programmed death (PD)-1 expression modulates T and B cell activation and is involved in maintaining peripheral tolerance. In this study, we examined the effects of a fully human PD-1-abrogating antibody on the in vitro expansion and function of human vaccine-induced CD8+ T cells (CTLs) specific for the melanoma-associated antigens glycoprotein 100 (gp100) and melanoma antigen recognized by T cells (MART)-1. PD-1 blockade during peptide stimulation aug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
136
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(143 citation statements)
references
References 47 publications
4
136
1
2
Order By: Relevance
“…33 PD-1 is expressed on postvaccination, melanoma antigen-specific, cytotoxic T lymphocytes (CTLs). 34 PD-1 blockade during peptide stimulation augmented the absolute numbers of vaccine peptide tetramer-positive CTLs. 34 Our study also demonstrated that PD-1-bearing, CD8-positive cells were increased in PBMCs and in the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…33 PD-1 is expressed on postvaccination, melanoma antigen-specific, cytotoxic T lymphocytes (CTLs). 34 PD-1 blockade during peptide stimulation augmented the absolute numbers of vaccine peptide tetramer-positive CTLs. 34 Our study also demonstrated that PD-1-bearing, CD8-positive cells were increased in PBMCs and in the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 93%
“…34 PD-1 blockade during peptide stimulation augmented the absolute numbers of vaccine peptide tetramer-positive CTLs. 34 Our study also demonstrated that PD-1-bearing, CD8-positive cells were increased in PBMCs and in the tumor microenvironment. The number of circulating PD-1-positive/CD8-positive T cells increased further as the disease progressed.…”
Section: Discussionmentioning
confidence: 93%
“…The variable regions of this antibody were sequenced and grafted onto human kappa and IgG4 constant region sequences containing an S228P mutation, and the resulting antibody (nivolumab) was expressed and purified from a transfected CHO cell line. The complete characterization of nivolumab is described below; preliminary data have been reported previously (25,30).…”
Section: Binding Analysis Of Nivolumab and Inhibition Of Ligand Bindingmentioning
confidence: 99%
“…We are currently exploring PD-1 disruption of T cells by generating CTLs targeting on specific tumor antigen, as to solve the problem that continuous treatment to interrupt PD-1/PD-L1 co-stimulation is needed in the process of sustained expansion of PD-1-expressing antigen-specific CTLs. 28 In recent years, a number of studies confirmed PD-L1 expression on the surface of gastric cancer cells 29,30 ; PD-1 expression in peripheral circulating blood lymphocytes, tumor-infiltrating lymphocytes, and its ligands; and PD-L1 in serum and tumor tissue. 31 The expression of PD-L1 and PD-1 was closely related with tumor progression, invasion, …”
Section: Discussionmentioning
confidence: 95%